The Cardiovascular-Mortality-Based Estimate for Normal Range of the Ankle-Brachial Index (ABI) - Peltonen Essi; Laivuori Mirjami; Vakhitov Damir; Korhonen Päivi; Venermo Maarit; Hakovirta Harri (MDPI, 2022)
Background: The ankle-brachial index (ABI) is a first-line examination in cardiovascular risk evaluation. Since cut-off values for normal ABI vary, the aim of the present study was to identify the cardiovascular-mortality-based estimate for the normal range of the ABI. After determining the reference range for the ABI, the corresponding toe-brachial index (TBI) and toe pressure for normal ABI were analyzed. Methods: All consecutive non-invasive pressure measurements in the vascular laboratory of a large university hospital 2011-2013 inclusive were collected and combined with patient characteristics and official dates and causes of death. Patients with an ABI range of 0.8-1.4 on both lower limbs were included in this study. Results: From 2751 patients, 868 had bilateral ABI values within the inclusion. Both ABI category ranges 0.80-0.89 and 0.90-0.99 had poorer survival compared to ABI categories 1.00-1.29 (p < 0.05). The 1-, 3-, and 5-year cardiovascular-death-free survival for respective ABI categories 0.80-0.99 vs. 1.00-1.29 were 90% vs. 96%, 84% vs. 92%, and 60% vs. 87%. The 1-, 3-, and 5-year overall survival for ABI categories 0.80-0.99 vs. 1.00-1.29 were 85% vs. 92%, 75% vs. 83%, and 42% vs. 74%. Conclusions: Borderline ABI (0.90-0.99) associates with higher overall and cardiovascular mortality compared to ABI values 1.00-1.29.